The sequential imperative : general cognitive principles and the structure of behaviour - Edmondson, William (Honorary Senior Research Fellow) (Value Inquiry Book Series, 2017)
In The Sequential Imperative William Edmondson explains how deep study of linguistics - from phonetics to pragmatics - can be the basis for understanding the organization of behaviour in any organism with a brain. The work demonstrates that Cognitive Science needs to be anchored in a linguistic setting. Only then can Cognitive Scientists reach out to reconsider the nature of consciousness and to appreciate the functionality of all brains. The core functionality of the brain - any brain, any species, any time - is delivery and management of the unavoidable bi-directional transformation between brain states and activity - the Sequential Imperative. Making it all work requires some general cognitive principles and close attention to detail. The book sets out the case in broad terms but also incorporates significant detail where necessary.